Influence of The Role of Government, Travel Barriers and Social Media Influencers on Visiting Interests With Destination Image as A Mediating Variable Study on Murung Batu Laba Tourism Visitors, Banjar Regency - Azizah, Fathia; Said, Laila Refiana (Program MM Universitas Surabaya, 2024)
Purpose: The purpose of this study was to investigate the impact of government role, travel barriers, and social media influencers on tourists' desire to visit Murung Batu Laba via the medium of destination image. Method: This study used quantitative research methods. A number of statistically significant connections were found between the dependent variables (destination image, social media influencers, government participation, and travel barriers) and the independent variables (interest in visiting the site). Both the destination's reputation and the attention of prospective tourists were directly impacted by social media influencers, according to the data. In contrast, travel limitations have the reverse impact on tourism and the destination's reputation, whereas government participation boosts both. Result: The results showed that destination image mediates the relationship between social media influencers and interest in visiting, as well as between travel hurdles and desire in visiting. This highlights the significance of the destination's image in attracting prospective tourists by mediating the attention of other elements.